Virtual reality used in English proficiency test based on apps - Bustam, MR; Nurfadillah, RA; Tsaniya, FN; Dewi, DN; Gaol, TVL (Journal of Language and Pragmatics Studies, 2022)
Today, the English Proficiency Test for both Tests of English as a Foreign Language (TOEFL) and International English Language Testing System (IELTS) become something important to people, especially for students who want to continue studying in universities within countries that use English as the first language. TOEFL and IELTS are used by the universities to assess the students' English language skills and are also used as indicators of whether they can understand and follow the lessons well later. Therefore, many institutions compete to develop their media and program array to become people's choice for testing their TOEFL and IELTS skills. The purpose of applying this virtual reality technology in the English Proficiency Test to utilize the function of virtual reality technology in English Proficiency Test such as TOEFL and IELTS based on Apps. In this case, we used a descriptive method to describe the problem faced when this idea is implemented. This idea's results are expected to increase the attractiveness, confidence using the Apps and finally boost the test score. Besides, it is expected that this virtual reality used in English Proficiency Test based on Apps can give the best experience to people who can't take the test in an offline institution.